Investigation of an anatomically variant isolated bicuspid pulmonary valve: A case report. Issue 52 (December 2017) - Ninomiya, Kenji; Fukasawa, Maki; Kawakami, Yuka; Fuke, Chiaki; Miyazaki, Tetsuji
Abstract: Introduction: We provide a discussion of the anatomical characteristics of the bicuspid pulmonary valve (BPV) in this paper. We performed an autopsy of an isolated BPV found in the heart of a deceased individual. The deceased was a man in his 60s and had no previous history of cardiovascular disease. The heart weighed 260 g and had mild right ventricular hypertrophy. The pulmonary valve had a fish-mouth-like shape that was convex to the pulmonary trunk and both cusps were thickened and hardened. The anterior and left semilunar cusps of the pulmonary valve were fused. Post-stenotic dilatation was noted. Conclusions: : In comparing the present case with previous reports, we found that, in human BPVs, cusps are fused in at least 2 patterns.